Biodiversity of the genus Cladophialophora - Badali, H. (CBS Fungal Biodiversity Centre, 2008)
Cladophialophora is a genus of black yeast-like fungi comprising a number of clinically highly significant species in addition to environmental taxa. The genus has previously been characterized by branched chains of ellipsoidal to fusiform conidia. However, this character was shown to have evolved several times independently in the order Chaetothyriales. On the basis of a multigene phylogeny (nucLSU, nucSSU, RPB1), most of the species of Cladophialophora (including its generic type C. carrionii) belong to a monophyletic group comprising two main clades (carrionii- and bantiana-clades). The genus includes species causing chromoblastomycosis and other skin infections, as well as disseminated and cerebral infections, often in immunocompetent individuals. In the present study, multilocus phylogenetic analyses were combined to a morphological study to characterize phenetically similar Cladophialophora strains. Sequences of the ITS region, partial Translation Elongation Factor 1-α and β-Tubulin genes were analysed for a set of 48 strains. Four novel species were discovered, originating from soft drinks, alkylbenzene-polluted soil, and infected patients. Membership of the both carrionii and bantiana clades might be indicative of potential virulence to humans.